An industrial reference fluid for moderately high viscosity - Oliveira, Carla Padrel de (2012)
In industrial practice, there is a demand for a reference standard for viscosity that is established for a readily available fluid to simplify the calibration of industrial viscometers for moderately high viscosities [(50 to 125) mPa · s]. Diisodecyl phthalate (DIDP) has been suggested as that reference fluid, and a number of studies of its properties have been carried out in several laboratories throughout the world, within the auspices of a project coordinated by the International Association for Transport Properties. That project has now progressed to the point where it is possible to collate the results of studies of the viscosity of the fluid by a number of different techniques, so as to lead to a proposed standard reference value which will be included in the paper. To support this recommended value, the various measurements conducted have been critically reviewed, and the sample purity and other factors affecting the viscosity have been studied. Density and surface tension measurements have also been performed. This paper does not describe the individual viscosity determinations carried out in independent laboratories because these are the subject of individual publications, but it does describe the ancillary studies conducted and their relevance to the viscosity standard. In addition, the paper contains recommended values for the viscosity of liquid DIDP. The samples of DIDP to which the recommended values refer are isomeric mixtures available commercially from certain suppliers, with a minimum purity by gas chromatography of 99.8 %. The recommended values result from a critical examination of all the measurements conducted to date and are supported by careful arguments dealing with the likely effects of the isomeric content of the sample as well as of other impurities. The proposed reference standard is intended particularly to serve an industrial need for a readily available calibration material with a viscosity close to that required in practical situations. To that end, the recommended value has an overall relative uncertainty of approximately 1 %. It is therefore not intended to supersede for the reference value for the viscosity of water at 20 °C, which is known much more accurately, but rather to complement it.